Development and optimization of enzyme linked immunoassays as readout system for activation of theileria parva-specific cytotoxic T lymphocytes. - Bateta, R. (Jomo Kenyatta University of Agriculture and Technology, 2004)
Immunity against Theileria parva in cattle is mediated by cytotoxic T lymphocytes (eTL) targeted at schizont-infected cells. Antigens expressed by the schizont stage of the parasite that induce protective immune response are possible candidates for sub-unit vaccine against ECF. Upon recognition and antigenic activation, CTLs releases cytokines and cytoplasmic granules containing granzyme and perf orin. Therefore the aim of this study was to develop enzyme linked immunosorbent assays (ELISA) to monitor release of cytokines and other cellular factors as a readout system for the activation of T. parva specific cytotoxic T lymphocytes. T. parva specific cytotoxic T lympocytes (CTL) were generated in the laboratory by repeated stimulation of PBMCs from immunized cattle with autologous irradiated T. parva infected cells. These cells were of CD8+ phenotype and lysed autologous T. parva infected cells as targets in 4hr 51chromium release assays. Presence of intracellular IFN-y, TNF-a and perf orin in these cells was demonstrated using intracellular staining. ELISA for detection of secreted forms of these cytokines were then developed and optimized using cytokine specific monoclonal antibodies and recombinant cytokines. IFN-y ELISA that was developed was capable of detecting recombinant bovine IFN-y as low as 120pglml. We compared IFN-y ELISA with IFN-y bioassay and it was found out that the sensitivity IFN-y ELISA was comparable to that of bioassay (100pglml). The TNF-a ELISA that was developed was not sensitive, since the detection limit of recombinant bovine TNF-a was 3.9nglml. Perf orin ELISA was developed using reagents against human perf orin and there was only an indication that perf orin was present in tissue culture supernatants from co-cultures of CTLs and 100% TpM. Attempts to develop a bovine Granzyme B (GrB) ELISA were not successful as the reagents against human GrB did not cross react with bovine as indicated in lack of intracellular staining of CTLs. Results showed that IFN-y ELISA can be used to detect IFN-y in supernatants after co-culture of CTLs and TpMs, in serum and lymph samples. TNF-a ELISA needs further development by testing more anti-bovine TNF-a reagents to improve the sensitivity. Development of sensitive perf orin and GrB ELISA will depend on availability of specific anti-bovine reagents.